DYSTOCIA DUE TO PEROSOMUS HORRIDUS MONSTER FETUS IN A MARWARI GOAT (Capra hircus) - A CASE REPORT - Tirpathi, Ashutosh; Mehta, JS (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
Perosomus horridus is a fetal monster, characterized by a lateral and downward multiple bending of spine from occiput to the sacrum. The vertebrae are definitely abnormal, shortened and ankylosed. The limb, neck and tail are ankylosed and deformed (Roberts, 1986). Such monsters have been occasionally reported in bovine and caprine (Arthur et al., 2001; Balasubramanian et al., 1995) and buffalo (Napolean et al., 2008; Singh et al., 2010; Jana and jana, 2010 and Solanki et al., 2010 ). Three cases of curved vertebral spine associated with deformed limbs were observed in Muzzaffarnagari sheep (Singh and Purbey, 1984). Such monsters cause difficulty in their delivery due to the curved spine and often die during delivery or soon after their birth. The present report describes a Perosomus horridus monster that resulted in dystocia in a primiparous Marwari goat.